LEAD AND MERCURY ALTERS LIPID CONTENTS IN LIVER AND KIDNEY OF HETEROPNEUSTES FOSSILIS - GAUTAM, R.K.; PARIHAR, RITESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1966)
The toxic effect of lead nitrate (Pb NO3) and mercuric nitrate (HgNO3) on the activity of a few lipids like phospholipids, Neutral Lipids in the liver and kidney of Heteropneustes fossilis have been analysed histochemically. Impact of these heavy metals on hepatic and nephric tissues interfere with protein and lipid metabolism. Our experimental evidences may be useful in revealing the mechanism of injury caused by these heavy metals.